O itinerário místico de Ernesto Cardenal - Teixeira, Faustino Luiz Couto (Revista eclesiástica brasileira, 2013)
Known in Latin America and in the Caribbean as a revolutionary poet, Ernesto Cardenal (1925-) produced during his life works in prose and verse that are equally marked by a significant mystical density. It is now essential to try and capture along this singular trajectory the traits of this spiritual presence that most probably is at the base of the richness and expressivity of his life and theoretical production. The Nicaraguan poet is now recognized by various authors as one of the most productive and original poets of the 20th century and it is of paramount importance to unveil the contemplative coordinates present in his rich narrative.